Generating (2,3)-codes - Anisimov, A.V. (Кибернетика и системный анализ, 2020)
The (2,3)-representation of integers utilizes the mixed numeration base of the radix-2 and the auxiliary radix-3. This representation yields a universal prefix-free binary encoding of all natural numbers with a variety of useful properties: robustness (self-synchronization), local error corrections, statistic regularities of code parameters, etc. The paper describes a procedure of monotonic generation of (2,3)-codewords in ascending order of their lengths. У (2,3)-поданні цілих чисел використано змішану систему числення за базисом 2 та допоміжним базисом 3. Це представлення породжує універсальне безпрефіксне двійкове кодування усіх натуральних чисел з багатьма корисними властивостями: робастність (самосинхронізація), локальні виправлення помилок, статистичні закономірності параметрів коду тощо. Описано процедуру монотонного генерування (2,3)-кодових слів у порядку зростання їхніх довжин. В (2,3)-представлении целых чисел использована смешанная система счисления по основанию 2 и вспомогательному основанию 3. Это представление порождает универсальное префиксно-свободное двоичное кодирование всех натуральных чисел, которое имеет много полезных свойств: робастность (самосинхронизация), локальные исправления ошибок, статистические закономерности параметров кода и т. п. Описана процедура монотонной генерации (2,3)-кодовых слов в порядке возрастания их длин.